The The Effect of Content Marketing and Influencer Endorsements on Purchasing Decisions for Wardah Skincare Products on the Shopee Marketplace: A Case Study of the Community in Subang District: The Effect of Content Marketing and Influencer Endorsements on Purchasing Decisions for Wardah Skincare Products on the Shopee Marketplace: A Case Study of the Community in Subang District - Devy Widya Apriandi; Nopa Nurdiansyah (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study aims to analyze the influence of Content Marketing and Influencer Endorse on purchase decisions of Wardah skincare products in the Shopee marketplace, both partially and simultaneously. The research method used is quantitative with a descriptive-verificative approach. Primary data were obtained through online questionnaires distributed to 75 respondents from the Subang District community. Data analysis was conducted using multiple linear regression, t-test, and F-test with SPSS 25. The results show that Content Marketing (X1) has a positive and significant effect on purchase decisions, with a regression coefficient of 0.284 and a significance value of 0.000 (<0.05). Meanwhile, Influencer Endorse (X2) has a positive but not significant effect on purchase decisions, with a regression coefficient of 0.168 and a significance value of 0.144 (>0.05). Simultaneously, Content Marketing and Influencer Endorse have a significant effect on purchase decisions, with an F-value of 73.975 and a contribution of 66.4%, while the remaining 33.6% is influenced by other factors not examined in this study. Thus, Content Marketing is the dominant factor influencing consumers’ purchase decisions of Wardah products on Shopee, while Influencer Endorse still plays a role but its contribution is not statistically strong.